Development of the novel and superior adaptive beam-loading compensation system calculated in the frequency domain for the J-PARC Linac. (1st November 2022) - Futatsukawa, K.; Cicek, E.; Fang, Z.; Fukui, Y.; Mizobata, S.; Sato, Y.
Abstract: The Japan Proton Accelerator Research Complex (J-PARC) is one of the highest intensity proton accelerator facilities in the world. Its accelerator consists of a 400-MeV linac (LINAC), a 3-GeV rapid-cycling synchrotron (RCS), and a 30-GeV main ring (MR) and its beam is provided for wide-ranging applications. The peak current of the beam at LINAC had been increased from 30 mA to the design value of 50 mA in 2018. Therefore, the performance of the beam-loading compensation implementing in the low-level radio frequency (LLRF) system has been more important to satisfy the stability of the accelerating gradient. Although the iterative learning control (ILC) scheme with adaptive ability was demonstrated, the practical use of ILC was not convenient for large accelerators such as the J-PARC LINAC with forty-nine RF stations. Therefore, we developed at novel and superior adaptive beam-loading compensation system that was calculated in the frequency domain. Compared to the scheme of the previous ILC, the newly developed system is useful because it does not require parameter adjustment using the beam. In the experimental results utilizing this system, the optimum tables of FF_BEAM were able to be obtained as a smaller number of iterations. The peak-to-peak stability of amplitude was achieved to ± 0.23% and the peak-to-peak stability of phase was improved to ± 0.036°. In addition, errors such as white noise did not accumulate for the table of FF_BEAM and this system solved the problem of the divergence when the number of iterations was increased. This implementation of the adaptive beam-loading compensation system calculated in the frequency domain will potentially contribute to the improvement of the J-PARC LINAC LLRF, and this system may lead to a stable user operation. This system is so simple in principle and effective that it could be applied to other linear accelerators with the pulsed beam.